The Effectiveness of Skills for Adolescents with Healthy Sexuality (SAHS) Program on Reducing the Risk of HIV Transmission among Adolescents - Heni Purnama; Irma Darmawati; Linlin Lindayani (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2018)
Introduction: The number of new HIV case is increasing significantly in Indonesia as compared toother countries in South East Asia region. Unsafe sexual behaviors become the critical risk factors for HIV transmission and adolescent is one of the high-risk group of risky sexual behavior and using drug injection. However, few studies have been conducted to find out the effective intervention to reduce the risk of HIV transmission among adolescents in Indonesia. The purpose of this study was to determine the effectiveness of SASH program (Skills for adolescents with healthy sexuality in reducing the risk of HIV transmission among adolescents in Bandung. Methods: A quasi-experimental design was conducted at one of private high school in Bandung. The sample in this study were thirty students. Every participant completed a self-measure questionnaire of the Bahasa version, which consists of HIV-related knowledge, attitude, and behavior with 52 items. The analysis used univariate and bivariate analysis using a paired t-test. Results: Majority of them were female (76.7). We found that SAHS program significantly effective on increased the knowledge, attitude, and behavior of HIV transmission among adolescents (p< 0.005) with mean different between pre-and post-test was 3.2, 2.19, and 1.98, respectively. Conclusions: SASH program is effective to improve knowledge, attitude, and behaviors towards HIV prevention among adolescents. Future researches are needed to improve the sustainability of the program, such as through the development of integrated peer-educator and to use technology as the delivery and promotion media.Key Words: Adolescents, HIV, Prevention, Sexual Behavior.